Rational engineering of VS4 nanorod array on rose-shaped VS2 nanosheets for high-performance aluminium-ion batteries. Issue 83 (29th September 2022) - Wang, Yan; Shen, Zihan; Lin, Xirong; Ding, Qian; Huang, Xiaofei; Han, Tianli; Zhang, Huigang; Liu, Jinyun
Abstract : A novel VS2 @VS4 composed of a VS4 nanorod array in situ grown on rose-shaped VS2 nanosheets for a high-performance Al-ion battery cathode is developed, which indicates the potential for rational engineering of emerging composites for energy-storage. Abstract : High performance aluminium-ion (Al-ion) batteries are of wide interest owing to the high theoretical capacity, abundance of Al metal and good safety. Here, we develop a hierarchical VS2 @VS4 composed of a VS4 nanorod array in situ grown on VS2 rose-shaped nanosheets that displays a good electrochemical performance. The VS2 @VS4 cathode displays a high capacity of 162.7 mA h g −1 after 200 cycles at −10 °C, and keeps 116.5 mA h g −1 after 500 cycles at room temperature. Rate-performance at −10 °C shows a capacity retention rate of 90%, which indicates the potential for engineering high-performance energy-storage composites.